Essays in microeconomic theory - Frones Edeso, Luis (2021)
This thesis uses game theory and microeconomics to investigate empirical puzzles. In Chapter 1 we provide a formal model to explain why new legislation that has widespread quickly in the last decades failed to achieve its objectives in accordance to recent evidence. In Chapter 2 we uncover a new class of equilibria in the canonical social learning setting with endogenous timing of decisions. We argue how our results can offer a social learning explanation for two applications: delays in the adoption of policy measures during the Covid-19 pandemic, and the timing of investments in the venture capital industry. In Chapter 3 we provide a formal model to explain recent evidence that correlates high levels of residential segregation based on income with low intergenerational mobility.